2020
DOI: 10.1002/clc.23528
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia is not superior to sedation in clinical outcome and cost‐effectiveness for ablation of persistent atrial fibrillation

Abstract: Background The strategy of anesthesia used during ablation of atrial fibrillation (AF) remains controversial. This study aimed to compare sedation with general anesthesia (GA) for catheter ablation of AF. Hypothesis The presence of AF is associated with an increased risk of stroke and heart failure and decreased quality of life and survival. Methods We carried out a retrospective single‐centered study with 351 patients undergoing the first ablation procedure for AF under sedation or GA. The main outcome was fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In addition, three studies published too long ago were excluded because ablation techniques and materials have changed and lack guidance for current clinical practice. The remaining 10 studies, comprising two RCTs [ 22 , 23 ] and 8 observational studies [ 13 – 15 , 17 , 24 27 ] satisfied the inclusion criteria and were eventually included in this meta-analysis. The literature search was conducted by two independent researchers (NP and JG).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, three studies published too long ago were excluded because ablation techniques and materials have changed and lack guidance for current clinical practice. The remaining 10 studies, comprising two RCTs [ 22 , 23 ] and 8 observational studies [ 13 – 15 , 17 , 24 27 ] satisfied the inclusion criteria and were eventually included in this meta-analysis. The literature search was conducted by two independent researchers (NP and JG).…”
Section: Resultsmentioning
confidence: 99%
“…CA of AF can be performed either under different anesthesia methods, but it is still controversial [ 16 , 24 , 28 ]. This meta-analysis systematically compared the clinical benefits and safety of GA/deep sedation and CS by procedural time, recurrence rate, and adverse event risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The substantial deep negative intrathoracic pressure during obstructive apnea may lead to air embolization through the blood access sheath 46 . Although the effectiveness of catheter ablation under general anesthesia has been reported, 47 general anesthesia is not widely performed in Japan because of the total time, cost, and insurance concerns associated with the procedure 48 . The J‐CARAF study revealed that only 2.9% of the total 10,795 ablation procedures were performed under general anesthesia 49 .…”
Section: Management Of Sleep Apnea (Catheter Ablation Of Af and Osa)mentioning
confidence: 99%